PENGIMPLEMENTASIAN DANPERANCANGAN SISTEM INFORMASI PENGONTROLAN PEMAKAIAN RUANG INAP PUSKESMAS MUARO KIAWAI KEC. GUNUNG TULEH JAMBI - Sophian, Sophan (Jurnal EDik Informatika, 2015)
In the development of information technology adult is really needed skill, the ability and resources that broad thought to confront the developments that are rapidly increasing .So also with every aspect of life at Indonesia today.Although most on the respective regions in indonesia having different geographical but we should have a system that kept changing . On regions Muaro Kiawai Kec .Jambi Gunung Tuleh Puskesmas that there is not yet have a system of information that can help officers as well as nurses take care of there to generate reports as well as perform the process of rapid penginputan. And was development in a system that can ease duty nurse there. Both in data entry process room, patient data and data doctors. Once learned, the authors draw the conclusion that in applying the computerized system in this case, Programming Language Visual Basic and Database MySQL is the appropriate application, because these applications is very easy in the process of transactions and reports.